The Appropriate FEC Parity Amount to Guarantee High Quality for Video Streaming - Al-Shugran, Mahmoud Ali Ibrahim (2009)
Efficiency and capability of forward error correction (FEC) mechanism to recover from losses, is the main idea behind its utilization in Real-time applications like video streaming over Internet. The number of Internet users continue to increase every day, thus network traffic will increase. Such increasing in network traffic will cause network congestion to increase, increasing in network congestion make data loss obvious problem that affect streaming video presentation quality. The efficiency of FEC mechanism come from the reduction of the time needed to recover lost packets, and there is no need for an additional channel for retransmission. The goal of FEC is to add redundancy that can be used to recover from packet loss in multimedia application, this big task for FEC comes with main condition; to achieve acceptable and the desired quality of presentation, FEC has to be introduced with minimum overhead for real-time application. However, depending on the fact that packet loss is often unknown and time varying. So, the amount of extra data that will be sent with the original data in the FEC block is predetermined comparing to the loss, hence loss recovery rate depends on the amount of redundancy data. For this reason FEC may take three characteristics depending on the amount of redundant data, effective (if the redundant is sufficient to the lost data), ineffective (if the redundant is too little to the lost data), or inefficient (if the redundant is too much to the lost data). Our research will concentrate on this problem to propose a suitable solution, by matching the appropriate redundancy that can achieve effectiveness, through sending the proposed FEC parity amount aside with the original data of video application. Proposed results will guarantee minimum packet loss and packet loss ratio in streaming application for video. Furthermore, through this study we will verify the affect of variance amount of redundancy data on the loss recovery rate, to find the appropriate parity amount, which can be effective in the presence of data loss. During that, Simulation results will demonstrate our progress for this project step by step to insure the works. Through extensive simulation, we will evaluate the scalability of the chosen redundancy data amount to improve aggregate FEC performance through video transmission.